A qualitative study exploring participants’ experiences of the SCOPE2 trial: chemoradiotherapy dose escalation in oesophageal cancer - Daniella Holland-Hart; Mirella Longo; Sarah Bridges; Lisette Nixon; Maria Hawkins; Tom Crosby; Annmarie Nelson (Trials)
Abstract Introduction This qualitative study explored patients’ experiences and perceptions of the SCOPE2 trial. The trial studied radiotherapy dose escalation in patients with inoperable oesophageal cancer treated with definitive chemo-radiation. SCOPE2 embedded a phase II trial for patients with a poor early response using positron emission tomography (PET) scans. Methods This longitudinal interview study took place between 2017 and 2021. Patients eligible for chemoradiotherapy were recruited from five clinical sites in the UK. Participants were invited to participate in three semi-structured interviews across four different time points: baseline (before treatment) and at 2–3 months, 3–6 months or 6 months + after baseline. This paper focuses on recruitment to the trial, practical management, the impact of COVID-19 and reflections of being on the trial. Real-time reporting to the trial team was used to inform potential improvements to trial conduct and recruitment. The interviews were thematically analysed. Results Ten participants were interviewed in 16 longitudinal interviews. There were five female and five male interview participants; three participants were accompanied by companions during their interviews. Recruitment to the trial and qualitative study was challenging. Motivations for joining the trial included altruism, potentially receiving better care and monitoring and the opportunity to improve their quality of life. Participants required adequate time to consider information and regular updates regarding trial and treatment process. Participants felt that their trial experience was minimally impacted by COVID-19, although some delays to treatment were reported. Conclusion Increased opportunities for patients to discuss and receive appropriate and timely information from trial staff and third sector partners could enhance patients’ understanding of future trials, treatments and procedures. Slow recruitment to the trial and qualitative study was further impeded by the COVID-19 pandemic and future trials would benefit from a more fully integrated approach to qualitative recruitment. Clinical trial registration ClinicalTrials.gov: NCT02741856 registered on 12 April 2016; ISRCTN: 9,712,546 registered on 26 October 2016.